An Economic Evaluation of Thread Embedding Acupuncture for the Treatment of Lumbar Herniated Intervertebral Disc in a Randomized Controlled Clinical Trial - Ha-Na Kim; Jun-Yeon Kim; Kyeong-Ju Park; Ji-Min Hwang; Jun-Yeong Jang; Min-Gi Jo; Min-Jung Ko; Sang-Yeup Chae; Jung-Hyun Kim; Bonhyuk Goo; Yeon-Cheol Park; Byung-Kwan Seo; et al. (Journal of Acupuncture Research, 2021)
Background Lumbar herniated intervertebral disc (LHIVD) is a frequently presented condition/disease in Korean medical institutions. In this study, the economics of thread embedding acupuncture (TEA) was evaluated in a randomized controlled trial comparing TEA with sham TEA (STEA). Methods This economic evaluation was analyzed from a limited social perspective, and the per-protocol set was from a basic analysis perspective. The cost-effectiveness analysis was based on the change in visual analog scale score, and the cost-utility analysis was based on the quality-adjusted life years. The final results were expressed as the average cost-effectiveness ratio and incremental cost-effectiveness ratio, and furthermore sensitivity analysis was performed to confirm the robustness of the results observed. Results The cost-effectiveness analysis showed that TEA was 9,908 won lower than STEA, while the decrease in 100 mm visual analog scale score was 8.5 mm greater in the TEA group compared with the STEA group (p > 0.05). The cost-utility analysis showed that TEA was 9,908 won lower than STEA, while the quality-adjusted life years of TEA was 0.0026 years higher than STEA (p > 0.05). These results were robust in the sensitivity analysis, but were not statistically significant. Conclusion In treating LHIVD, TEA appeared to have cost-effectiveness and cost-utility compared with STEA. However, there were no significant differences between the groups in terms of cost, effectiveness, and utility indicators. Therefore, results must be interpreted prudently; this study was the 1st to conduct an economic evaluation of TEA for LHIVD.